ECO-Syria Workshop Report Green Transitional Justice in Post-Assad Syria - Dinc, Pinar ; 0000-0001-9731-2470; Nardi, Maria Andrea ; 0000-0002-9860-6347; Hamza, Mo ; 0000-0002-1908-1627; Eklund, Lina; Abdi, Abdulhakim M. ; 0000-0001-6486-8747; Sardar, Purnendu ; 0000-0001-5491-3700 (CMES (Center for Middle Eastern Studies, Lund University, 2025)
The aim of this workshop report is to move beyond existing academic discussions on environmental politics in North and East Syria3, and to respond directly to the region’s urgent environmental needs and challenges, and to explore possible pathways for ecological recovery and justice. We seek to critically examine the political, social, and ecological dimensions of environmental governance in post-conflict Syria, and to propose context-sensitive recommendations that prioritize local agency, equity, and long-term ecological well-being.